Long-Term Biostability of Self-Assembling Protein Polymers in the Absence of Covalent Crosslinking - Sallach, Rory E. (2009)
Unless chemically crosslinked, matrix proteins, such as collagen or silk, display a limited lifetime in vivo with significant degradation observed over a period of weeks. Likewise, amphiphilic peptides, lipopeptides, or glycolipids that self-assemble through hydrophobic interactions to form thin films, fiber networks, or vesicles do not demonstrate in vivo biostability beyond a few days. We report herein that a self-assembling, recombinant elastin-mimetic triblock copolymer elicited minimal inflammatory response and displayed robust in vivo stability for periods exceeding 1 year, in the absence of either chemical or ionic crosslinking. Specifically, neither a significant inflammatory response nor calcification was observed upon implantation of test materials into the peritoneal cavity or subcutaneous space of a mouse model. Moreover, serial quantitative magnetic resonance imaging, evaluation of pre- and post-explant ultrastructure by cryo-high resolution scanning electron microscopy, and an examination of implant mechanical responses revealed substantial preservation of form, material architecture, and biomechanical properties, providing convincing evidence of a non-chemically or ionically crosslinked protein polymer system that exhibits long-term stability in vivo.